Global vision of pediatric food allergies - Perego, Luis Héctor (Medwin Publishers Committed to Create Value for Researchers, 2020)
Editorial: Hypersensitivity caused by immune mechanisms is known as an allergic state and may occur if several factors converge. Among them, family history, presence of allergens and environmental factors. These allergic states are expressed as clinical symptoms, observing atopic dermatitis, asthma, allergic rhinitis and food-induced allergies [1]. In the field of public health, it is important to identify food allergies and intolerances. In the last decade s an incremental trend of this type of pathology was observed. s The lack of definitive therapies for the healing of these allergies finds in the prevention the most appropriate way for their treatment; being an effective strategy the elimination allergens from the diets of individuals with sensitivity to elements that are triggered by adverse effects effectors adversos [1].
Keywords: Alergias alimentarias; Pediatría